Smart Traffic Light based on IoT and mBaaS using High Priority Vehicles Method - Muhammad Izzuddin Mahali; Eko Marpanaji; Satriyo Dewanto; Bekti Wulandari; Umi Rochayati; Nur Hasanah (IAES Indonesia Section, 2018)
An increase of the number of vehicles which is not followed by the number of roads can lead to the increase of congestion, especially in big cities. Regulation of law no 22 Year 2009 explains that there are seven types of vehicles prioritized on the road. This research aims to build a Smart Traffic Light as a solution with the goal of making the prioritized vehicle journey smooth when crossing the road with Smart Traffic Light. The proposed system is